Harnessing the Endogenous 2μ Plasmid of Saccharomyces cerevisiae for Pathway Construction - Yang, Jing; Tian, Yujuan; Liu, Huayi; Kan, Yeyi; Zhou, Yi; Wang, Ying; Luo, Yunzi (Frontiers in Microbiology, 2021)
pRS episomal plasmids are widely used in Saccharomyces cerevisiae, owing to their easy genetic manipulations and high plasmid copy numbers. Nevertheless, the broader application is hampered by the instability of the pRS plasmids. In this study, we designed an episomal plasmid based on the endogenous 2μ plasmid with both improved stability and increased plasmid copy number, naming p2μM, 2μ modified plasmid. In the p2μM plasmid, an insertion site between the REP1 promoter and RAF1 promoter was identified, where the replication (ori) of Escherichia coli and selection marker gene of Saccharomyces cerevisiae were inserted. As a proof of concept, the tyrosol biosynthetic pathway was constructed in the p2μM plasmid and in a pRS plasmid (pRS423). As a result, p2μM plasmid presented lower plasmid loss rate than that of pRS423. Furthermore, higher tyrosol titers were achieved in S. cerevisiae harboring p2μM plasmid carrying the tyrosol pathway-related genes. Our study provided an improved genetic manipulation tool in Saccharomyces cerevisiae for metabolic engineering applications, and this tool may be widely applied for valuable products biosynthesis in yeast.